Socio-Economic Impacts Of Sarawak Homestay Industry - Muhammad Fekri, Taib (Universiti Malaysia Sarawak (UNIMAS), 2013)
This study is designed to examine the socio-economic impacts of Sarawak homestay industry. The data set in this study was collected from the homestay participants through questionnaire and interview. There are 83 homestay participants had become sample for this study. The methodology that had been used in this study to analyze the data included descriptive analysis, reliability analysis, One-Way ANOVA and factor analysis. Empirical result shows that income generated by homestay industry had significant relationship with the education, numbers of room and charges. Besides, job and business opportunities as well as socio economic development are the visible impacts towards homestay participants. This research also highlights the most challenges faced by homestay participants to make homestay industry successful. Several recommendations had been point out for homestay participants in order to improve the homestay service in the future.